High School Students Perceptions: Inspiring and Uninspiring Teachers’ Interpersonal Communication (IPC) in TEFL - Sri Ananda Pertiwi; Rawuh Yuda Yuwana (Departement of Mathematics Education, 2023)
This study examined high school students’ views of their teachers using interpersonal communication in Teaching English as Foreign Language (TEFL). The respondents involved 38 students as reached saturated data, which were taken from six classes taught by two EFL teachers (male and female) at a high school in South Sulawesi province, Indonesia. A semi-structured interview was employed with students to collect the data. The semi-structured interview data were categorized and reported descriptively according to DeVito's (1997) effective interpersonal communication: openness, empathy, supportiveness, positive feelings, and equality. This study reveals that students' perception shows that both teachers conduct favorable and unfavorable interpersonal communication verbally or non-verbally in TEFL. This study also indicates that teachers’ cross-gender using nonverbal communication perceives as an inconvenience, touch, and personal space. These contrarieties propose that teachers consider their students’ culture, beliefs, or preferences while utilizing interpersonal communication in TEFL, especially personal space and touch at the high school level.